PERSONAL ATTRIBUTES AND SITUATIONAL FACTORS AS PREDICTORS OF ORGANISATIONAL COMMITMENT: AN EXPLORATORY STUDY - Baldev R. Sharma; V. N. Srivastava And Sombala NIngthoujam (Abhigyan, 2011)
Organisational commitment is one of the energising forces that contribute to motivated behaviour. With the help of data from a sample of 98 senior managers of a large Indian public sector undertaking in the transportation sector, this study has tried to ascertain the level of organizational commitment and to identify the predictors thereof. Whereas both personal attributes as well as situational factors were found to be the critical predictors, the latter had a greater role to play in influencing commitment than did the former. Though it is an exploratory study, its findings are in general accord with the findings of some of the earlier studies.